Regulation and function of Scr, exd, and hth in the Drosophila salivary gland. - Henderson, K.D.; Andrew, D.J. (Developmental Biology, 2000)
Salivary gland formation in the Drosophila embryo is dependent on the homeotic gene Sex combs reduced (Scr). When Scr function is missing, salivary glands do not form, and when SCR is expressed everywhere in the embryo, salivary glands form in new places. Scr is normally expressed in all the cells that form the salivary gland. However, as the salivary gland invaginates, Scr mRNA and protein disappear. Homeotic genes, such as Scr, specify tissue identity by regulating the expression of downstream target genes. For many homeotic proteins, target gene specificity is achieved by cooperatively binding DNA with cofactors. Therefore, it is likely that SCR also requires a cofactor(s) to specifically bind to DNA and regulate salivary gland target gene expression. Here, we show that two homeodomain-containing proteins encoded by the extradenticle (exd) and homothorax (hth) genes are also required for salivary gland formation. exd and hth function at two levels: (1) exd and hth are required to maintain the expression of Scr in the salivary gland primordia prior to invagination and (2) exd and hth are required in parallel with Scr to regulate the expression of downstream salivary gland genes. We also show that Scr regulates the nuclear localization of EXD in the salivary gland primordia through repression of homothorax (hth) expression, linking the regulation of Scr activity to the disappearance of Scr expression in invaginating salivary glands.